The Ginsenoside 20-O-β-D-Glucopyranosyl-20(S)-Protopanaxadiol Induces Autophagy and Apoptosis in Human Melanoma via AMPK/JNK Phosphorylation - Kang, Soouk (Public Library of Science, 2014)
Studies have shown that a major metabolite of the red ginseng ginsenoside Rb1, called 20-O-β-D-glucopyranosyl-20(S)-protopanaxadiol (GPD), exhibits anticancer properties. However, the chemotherapeutic effects and molecular mechanisms behind GPD action in human melanoma have not been previously investigated. Here we report the anticancer activity of GPD and its mechanism of action in melanoma cells. GPD, but not its parent compound Rb1, inhibited melanoma cell proliferation in a dose-dependent manner. Further investigation revealed that GPD treatment achieved this inhibition through the induction of autophagy and apoptosis, while Rb1 failed to show significant effect at the same concentrations. The inhibitory effect of GPD appears to be mediated through the induction of AMPK and the subsequent attenuation of mTOR phosphorylation. In addition, GPD activated c-Jun by inducing JNK phosphorylation. Our findings suggest that GPD suppresses melanoma growth by inducing autophagic cell death and apoptosis via AMPK/JNK pathway activation. GPD therefore has the potential to be developed as a chemotherapeutic agent for the treatment of human melanoma.